Azimuthal decorrelation of jets widely separated in rapidity - Abachi, S; Abbott, B; Abolins, M; Acharya, B; Adam, I; Adams, D; Adams, M; Ahn, S; Aihara, H; Alitti, J; Alvarez, G; Alves, G; et al. (1996)
This study reports the first measurement of the azimuthal decorrelation between jets with pseudorapidity separation up to five units. The data were accumulated using the DO detector during the 1992-1993 collider run of the Fermilab Tevatron at √s = 1.8 TeV. These results are compared to next-to-leading order (NLO) QCD predictions and to two leading-log approximations (LLA) where the leading-log terms are resummed to all orders in αS. The final state jets as predicted by NLO QCD show less azimuthal decorrelation than the data. The parton showering LLA Monte Carlo HERWIG describes the data well; an analytical LLA prediction based on Balitsky-Fadin-Kuraev-Lipatov resummation shows more decorrelation than the data.